Transforming tribal farming from subsistence to sustainable - Reddy, K S; Maruthi, V; Pankaj, P K; Pushpanjali, Pushpanjali; Krishna, T Sai (Indian Farming, 2020)
The tribal regions in Telangana are endowed with land degradation, acute shortage of water for both agriculture and drinking, low income, subsistence farming and malnutrition covering almost 1,174 villages with a total population of 31.78 lakh accounting for 9.08% of the total state population. In these areas, rain dependent agriculture is extensively followed by the tribal farmers with productivity levels far less than state average of 0.8-1.0 t/ha. The weather aberration in terms of increased dry spells immediately after germination of the crops during rainy season, changed pattern of rainfall with high intensity for short durations, shift in the occurrence of monsoon rainfall, decrease in rainy days etc. are very common due to the climate change impacts in the region.